Pengaruh Efektivitas Good Corporate Governance Dan Kinerja Lingkungan Terhadap Kinerja Perusahaan - Arie Gales, Frans; Wulandari, Ika (GEMA EKONOMI, 2023)
The purpose of this research is to obtain facts about how the performance of coal mining companies from 2018 to 2022 is influenced by independent commissioners, boards of directors, audit committees, and environmental performance. This research examines the impact of environmental performance and effective corporate governance on business performance. A total of 13 coal mining sub-sector companies listed on the IDX in 2018–2022 were the research samples. Collecting data for research using secondary sources and purposive sampling. SPSS 21 was applied to test the data. Statistical tests are applied during the data processing stage of this method. Multiple linear regression analysis reveals that the factors of independent commissioners, board of directors, and audit committees have a significant and beneficial impact on organizational performance. The t test with the results of the study also shows that the independent commissioner variable has a significant impact on company performance, the board of directors has a significant impact on company performance, and the audit committee has a significant impact on company performance partially